Ginseng extract improves pancreatic islet injury and promotes β-cell regeneration in T2DM mice - Yin, Jianying; Huang, Yuanfeng; Wang, Ke; Zhong, Qin; Liu, Yuan; Ji, Zirui; Liao, Yiwen; Ma, Zhiyuan; Bei, Weijian; Wang, Weixuan (Frontiers in Pharmacology, 2024)
Panax ginseng C. A. Mey. (Araliaceae; Ginseng Radix et Rhizoma), a traditional plant commonly utilized in Eastern Asia, has demonstrated efficacy in treating neuro-damaging diseases and diabetes mellitus. However, its precise roles and mechanism in alleviating type 2 diabetes mellitus (T2DM) need further study. The objective of this study is to explore the pharmacological effects of ginseng extract and elucidate its potential mechanisms in protecting islets and promoting β-cell regeneration. The T2DM mouse model was induced through streptozotocin combined with a high-fat diet. Two batches of mice were sacrificed on the 7th and 28th days following ginseng extract administration. Body weight, fasting blood glucose levels, and glucose tolerance were detected. Morphological changes in the pancreatic islets were examined via H & E staining. Levels of serum insulin, glucagon, GLP-1, and inflammatory factors were measured using ELISA. The ability of ginseng extract to promote pancreatic islet β-cell regeneration was evaluated through insulin & PCNA double immunofluorescence staining. Furthermore, the mechanism behind β-cells regeneration was explored through insulin & glucagon double immunofluorescence staining, accompanied by immunohistochemical staining and western blot analyses. The present research revealed that ginseng extract alleviates symptoms of T2DM in mice, including decreased blood glucose levels and improved glucose tolerance. Serum levels of insulin, GLP-1, and IL-10 increased following the administration of ginseng extract, while levels of glucagon, TNF-α, and IL-1β decreased. Ginseng extract preserved normal islet morphology, increased nascent β-cell population, and inhibited inflammatory infiltration within the islets, moreover, it decreased α-cell proportion while increasing β-cell proportion. Mechanistically, ginseng extract might inhibit ARX and MAFB expressions, increase MAFA level to aid in α-cell to β-cell transformation, and activate AKT-FOXM1/cyclin D2 to enhance β-cell proliferation. Our study suggests that ginseng extract may be a promising therapy in treating T2DM, especially in those with islet injury.